Manganese-based adsorption material preparation method and hydrogen purification method

Preparing graphite oxide through an improved Hummer method and obtaining manganese-based adsorbent materials through hydrothermal treatment solves the problem of poor effectiveness of existing hydrogen desulfurization technology, achieves efficient removal of sulfides in hydrogen under low temperature conditions, and meets the requirements of hydrogen for fuel cells. Strict requirements.

CN119327417AActive Publication Date: 2025-01-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202310886689.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-21
Estimated Expiration
2043-07-18

AI Technical Summary

Technical Problem

The existing hydrogen desulfurization technology has poor effect, complex process and high cost, making it difficult to effectively remove trace sulfides in hydrogen, affecting the efficiency of fuel cells.

Method used

The improved HUMMER method is used to prepare the oxygenum filtering of the original solution, and the manganese -based adsorption material is obtained through water heat treatment. The hydrogen purification is used to use the material at a temperature below 50 ° C to effectively remove the constant sulfide in the hydrogen.

Benefits of technology

Achieved sulfide in hydrogen under low temperature conditions under low temperature conditions. The purified hydrogen can be directly used for hydrogen supply of fuel cells, meet the requirements of strict sulfide content, and reduce preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327417A_ABST
    Figure CN119327417A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a manganese-based adsorption material and graphite oxide, and the method comprises the following steps: preparing graphite oxide by adopting an improved Hummer method, and carrying out solid-liquid separation on the obtained material to obtain a filtered stock solution and graphite oxide; and performing hydrothermal treatment on the filtering stock solution under hydrothermal self-generated pressure and atmosphere, and recovering a solid-phase material to obtain the manganese-based adsorption material. According to the preparation method disclosed by the invention, the use amount of potassium permanganate is relatively high when the improved Hummer is prepared, so that the manganese-based adsorption material can be prepared without adding a manganese source, and the preparation cost is reduced. The manganese-based adsorption material prepared by the method shows excellent performance in the hydrogen purification reaction process, constant sulfides (the volume content is greater than 0.1%) in hydrogen can be removed at the temperature of lower than 50 DEG C, and the purified hydrogen can be directly used for hydrogen supply of a fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of hydrogen purification, and specifically relates to a method for preparing a manganese-based adsorption material and a method for purifying hydrogen. Background Art

[0002] Hydrogen is an important energy source. One of the uses of hydrogen is to supply hydrogen to fuel cells and generate electricity to realize the utilization of hydrogen energy. However, the electrode catalysts of fuel cells are sensitive to sulfides. The presence of trace amounts of sulfides will poison the electrode catalysts of fuel cells, thereby reducing their efficiency. Therefore, strict requirements are placed on the sulfide content of hydrogen used in fuel cells. The international requirement is that the sulfide content calculated as hydrogen sulfide must be less than 4ppb, which is the most stringent requirement for the impurity content in hydrogen used in fuel cells. How to ensure that the sulfide content of hydrogen used in fuel cells is qualified is the technical key to using hydrogen in fuel cells. Existing desulfurization technologies are mostly for gases such as natural gas, while there are fewer methods for treating sulfides in hydrogen, and there are also problems such as poor desulfurization effect, complex treatment process, and high cost. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a manganese-based adsorption material and a method for purifying hydrogen. The preparation method of the present invention is to perform hydrothermal treatment on a filtered stock solution of graphite oxide prepared by an improved Hummer method (increasing the amount of potassium permanganate, and not adding sodium nitrate and hydrogen peroxide). Since the amount of potassium permanganate used in preparing graphite oxide by the improved Hummer method is relatively high, a manganese-based adsorption material can be prepared without adding an additional manganese source, thereby reducing the preparation cost of the manganese-based adsorption material. The manganese-based adsorption material prepared by the present invention exhibits excellent performance in the hydrogen purification reaction process, and can achieve the removal of constant sulfides (volume content>0.1%) in hydrogen at a temperature below 50°C, and the purified hydrogen can be directly used for hydrogen supply to fuel cells.

[0004] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a manganese-based adsorbent material and graphite oxide, the method comprising:

[0005] S1 uses an improved Hummer method to prepare graphite oxide, and the obtained material is subjected to solid-liquid separation to obtain a liquid phase and a solid phase respectively. The liquid phase is the filtered stock solution, and the solid phase is recovered to obtain graphite oxide;

[0006] S2 hydrothermally treat the filtered stock solution under hydrothermal autogenous pressure and atmosphere and recover the solid phase material to obtain a manganese-based adsorption material;

[0007] When preparing graphite oxide, the mass ratio of potassium permanganate to graphite is greater than 6.5.

[0008] Optionally, sodium nitrate and hydrogen peroxide are not added during the reaction process of the improved Hummer method.

[0009] Optionally, the oxygen content of the graphite oxide is 35-60% by weight, and the carbon content is 40-65% by weight. Optionally, the mass ratio of potassium permanganate to graphite is 8-15 when preparing the graphite oxide.

[0010] Optionally, in the filtered stock solution of the graphite oxide, the manganese content calculated as divalent manganese ions is 40-100 g / L, the potassium content calculated as potassium ions is 25-80 g / L, the sulfur content calculated as sulfate ions is 10-200 g / L, and the carbon content calculated as carbon atoms is 5-50 g / L.

[0011] Optionally, step S2 includes:

[0012] (1) mixing the filtered stock solution with optional water to obtain a mixed solution, wherein the mass ratio of the filtered stock solution to water is 1:(0-10);

[0013] (2) subjecting the mixed solution to hydrothermal crystallization treatment, taking out a solid product, washing, drying and optionally calcining it to obtain the manganese-based adsorption material;

[0014] Wherein, the hydrothermal crystallization conditions include: temperature of 100-200° C. and time of 2-72 h under autogenous pressure;

[0015] The calcination conditions include: temperature of 250-700° C., time of 1-12 hours, and pressure of 0.1-1 MPa.

[0016] The second aspect of the present invention provides a method for preparing a manganese-based adsorption material using the method provided by the first aspect of the present invention.

[0017] Optionally, in the XRD spectrum of the manganese-based adsorbent material, characteristic peaks exist at 2θ positions of 12.2±0.5°, 24.7±0.5°, 36.8±0.5° and 66.3±0.5°, respectively; the half-peak width of the diffraction peak at 12.2±0.5° is greater than 0.5°;

[0018] The specific surface area of ​​the manganese-based adsorption material is 200 to 350 m 2 / g, pore volume is 0.2-0.9 ml / g; preferably, specific surface area is 240-320 m 2 / g, and the pore volume is 0.4~0.7ml / g.

[0019] Optionally, based on the mass of the manganese-based adsorption material, the Mn element content in the manganese-based adsorption material is 25-53% by weight, the S element content is 1-15% by weight, and the K element content is 2-20% by weight;

[0020] Preferably, the Mn element content in the manganese-based adsorption material is 40-53% by weight, the S element content is 2-12% by weight, and the K element content is 6-15% by weight.

[0021] The third aspect of the present invention provides a method for purifying hydrogen, the method comprising: contacting hydrogen with the manganese-based adsorption material provided by the second aspect of the present invention at a temperature of 20 to 50° C. to carry out a purification reaction.

[0022] Optionally, the reaction conditions of the hydrogen purification method include: temperature of 20-50°C, pressure of 0.1-5.0 MPa, and space velocity of 50-10000 h -1 ;

[0023] The volume content of sulfide in the hydrogen is 0.1% to 1%, and the content of sulfide in the hydrogen is calculated as hydrogen sulfide.

[0024] Through the above technical scheme, the preparation method of the present invention performs hydrothermal treatment on the graphite oxide filter stock solution prepared by the improved Hummer method, and optionally roasts to obtain a manganese-based adsorption material. Since the amount of potassium permanganate used in the preparation of graphite oxide by the improved Hummer method is relatively high, it not only speeds up the graphite oxidation process, but also simplifies the preparation steps of the manganese-based adsorption material, and does not require the addition of an additional manganese source, thereby reducing the preparation cost of the manganese-based adsorption material. The manganese-based adsorption material prepared by the present invention exhibits excellent performance in the hydrogen purification reaction process, and can achieve the removal of sulfides in hydrogen at a temperature below 50°C, and the purified hydrogen can meet the standard requirements for hydrogen used in fuel cells.

[0025] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0027] Figure 1 This is the XRD spectrum of the manganese-based adsorption material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0029] A first aspect of the present invention provides a method for preparing a manganese-based adsorbent material and graphite oxide, the method comprising:

[0030] S1 uses an improved Hummer method to prepare graphite oxide, and the obtained material is subjected to solid-liquid separation to obtain a liquid phase and a solid phase respectively. The liquid phase is the filtered stock solution, and the solid phase is recovered to obtain graphite oxide;

[0031] S2 hydrothermally treat the filtered stock solution under hydrothermal autogenous pressure and atmosphere and recover the solid phase material to obtain a manganese-based adsorption material;

[0032] When preparing graphite oxide, the mass ratio of potassium permanganate to graphite is greater than 6.5.

[0033] In one embodiment of the present invention, sodium nitrate and hydrogen peroxide are not added during the reaction process of the improved Hummer method.

[0034] In a specific embodiment of the present invention, the oxygen content of the graphite oxide is 35-60% by weight, preferably 40-55% by weight, and the carbon content is 40-65% by weight, preferably 45-60% by weight.

[0035] The graphite oxide prepared by the present invention has a high oxygen content, is easy to disperse, has many sheet defects, and has a strong chelating effect, and will have significant advantages in adsorbing heavy metal ions in wastewater and soil remediation.

[0036] The preparation method of the present invention performs hydrothermal crystallization treatment on the filtered stock solution of graphite oxide prepared by the improved Hummer method. Since the amount of potassium permanganate used in the preparation of graphite oxide by the improved Hummer method is relatively high, the speed of graphite oxidation is accelerated, and no additional manganese source needs to be added, thereby reducing the preparation cost of the manganese-based adsorption material.

[0037] In a specific embodiment of the present invention, the mass ratio of potassium permanganate to graphite during the preparation of graphite oxide is 8-15, preferably 9-12.

[0038] In a specific embodiment of the present invention, graphite and 98% concentrated sulfuric acid are added to a beaker placed in an ice water bath (<5°C) and stirred to mix evenly, potassium permanganate is slowly added in batches while stirring, and after adding potassium permanganate, the mixture is stirred and reacted in a warm water bath at 40°C for 0.5h, and then an appropriate amount of deionized water is added and the temperature of the water bath is raised to 95-98°C for 0.5h; the beaker is taken out of the water bath and deionized water of about 60°C is added, and stirring is continued to reduce the temperature to below 30°C, and after stirring evenly, the graphite oxide solid is filtered and separated to obtain a graphite oxide filtration stock solution; the dosage ratio of the above reactants is graphite: concentrated sulfuric acid: potassium permanganate: water = 1g: 15-35ml: 6.5-15g: 50-500ml.

[0039] In a specific embodiment of the present invention, in the filtered stock solution of graphite oxide, the manganese content calculated as divalent manganese ions is 40-100 g / L, preferably 50-80 g / L, the potassium content calculated as potassium ions is 25-80 g / L, preferably 35-60 g / L, the sulfur content calculated as sulfate ions is 10-200 g / L, preferably 40-100 g / L, and the carbon content calculated as carbon atoms is 5-50 g / L, preferably 8-20 g / L.

[0040] In a further preferred specific embodiment, the graphite oxide filtration stock solution is an aqueous solution, mainly containing elements such as manganese, potassium, sulfur, and carbon, wherein the manganese content calculated as divalent manganese ions is 64 g / L, the potassium content calculated as potassium ions is 37 g / L, the sulfur content calculated as sulfate ions is 102 g / L, and the carbon content calculated as carbon atoms is 6.5 g / L, wherein the main source of the carbon element is the soluble graphite oxide remaining in the stock solution.

[0041] In the present invention, the recovery process of the solid phase in step S1 to obtain graphite oxide refers to drying after an optional washing step. Washing is a conventional operation in the art, such as water washing; wherein the drying step is conventional drying, vacuum drying or freeze drying, wherein the conventional drying temperature is 80 to 200°C and the time is 1 to 48 hours; the vacuum drying temperature is 20 to 100°C and the time is 1 to 24 hours; the freeze drying temperature is -60 to -20°C and the time is 12 to 48 hours.

[0042] In a specific embodiment of the present invention, step S2 includes:

[0043] (1) mixing the filtered stock solution with optional water to obtain a mixed solution, wherein the mass ratio of the filtered stock solution to water is 1:(0-10), preferably 1:(1-5);

[0044] (2) subjecting the mixed solution to hydrothermal crystallization treatment, taking out a solid product, washing, drying and optionally calcining it to obtain the manganese-based adsorption material.

[0045] In a specific embodiment of the present invention, the hydrothermal crystallization conditions include: a temperature of 100 to 200° C., preferably 110 to 160° C., and a time of 2 to 72 hours, preferably 4 to 36 hours under autogenous pressure;

[0046] The calcination conditions include: a temperature of 250 to 700° C., preferably 300 to 500° C., a time of 1 to 12 hours, preferably 2 to 6 hours, and a pressure of 0.1 to 1 MPa, preferably 0.1 to 0.5 MPa.

[0047] The second aspect of the present invention provides a method for preparing a manganese-based adsorption material using the method provided by the first aspect of the present invention.

[0048] In a specific embodiment of the present invention, the XRD spectrum of the manganese-based adsorbent material has characteristic peaks at 2θ of 12.2±0.5°, 24.7±0.5°, 36.8±0.5° and 66.3±0.5° respectively; the half-peak width of the diffraction peak at 12.2±0.5° is greater than 0.5°;

[0049] The specific surface area of ​​the manganese-based adsorption material is 200 to 350 m 2 / g, pore volume is 0.2-0.9 ml / g; preferably, specific surface area is 240-320 m 2 / g, and the pore volume is 0.4~0.7ml / g.

[0050] In a specific embodiment of the present invention, based on the mass of the manganese-based adsorption material, the manganese-based adsorption material has a Mn content of 25-53% by weight, an S content of 1-15% by weight, a K content of 2-20% by weight, and the remainder is an O element;

[0051] Preferably, the Mn element content in the manganese-based adsorption material is 40-53% by weight, the S element content is 2-12% by weight, the K element content is 6-15% by weight, and the balance is O element.

[0052] The third aspect of the present invention provides a method for purifying hydrogen, the method comprising: contacting hydrogen with the manganese-based adsorption material provided by the second aspect of the present invention at a temperature of 20 to 50° C. to carry out a purification reaction.

[0053] In a specific embodiment of the present invention, the reaction conditions of the hydrogen purification method include: temperature of 20-50°C, pressure of 0.1-5.0 MPa, and space velocity of 50-10000 h -1 Preferably, the temperature is 25-40°C, the pressure is 1-3 MPa, and the air velocity is 100-5000 h -1 .

[0054] The volume content of sulfide in the hydrogen is 0.1% to 1%, and the content of sulfide in the hydrogen is calculated as hydrogen sulfide.

[0055] In the present invention, the hydrogen purification method is carried out under relatively low temperature, high concentration and low space velocity conditions, and the sulfide in the hydrogen is effectively removed at a temperature below 50°C. The sulfide content in the purified hydrogen can meet the requirements for the sulfide impurity content in hydrogen used in fuel cells.

[0056] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.

[0057] The reagents used in the present invention are all commercially available analytically pure reagents.

[0058] Example 1

[0059] a. Prepare graphite oxide by using an improved Hummer method. Add 5 g of graphite and 98% concentrated sulfuric acid to a beaker placed in an ice water bath (~5°C) and stir to mix evenly. Slowly add potassium permanganate in 5 batches while stirring to mix. After adding potassium permanganate, continue stirring in a warm water bath at 40°C for 0.5 h. Then, add an appropriate amount of deionized water and raise the temperature of the water bath to 95-98°C for 0.5 h. Take out the beaker from the water bath and add deionized water at about 60°C. Continue stirring to reduce the temperature to below 30°C. After stirring evenly, filter and separate the graphite oxide solid to obtain a graphite oxide filtration stock solution. The amount ratio of the above reactants is graphite: concentrated sulfuric acid: potassium permanganate: water = 1 g: 30 ml: 10 g: 100 ml. The obtained materials are subjected to solid-liquid separation to obtain a filtration stock solution liquid phase and a graphite oxide solid phase, respectively. The graphite oxide solid phase is vacuum dried at 80°C for 6 h to obtain a graphite oxide powder. Among them, the manganese content in the filtered raw liquid is 64g / L in terms of divalent manganese ions, the potassium content in terms of potassium ions is 37g / L, the sulfur content in terms of sulfate ions is 102g / L, and the carbon content in terms of carbon atoms is 6.5g / L; the oxygen content of the graphite oxide is 43% by weight, and the carbon content is 57% by weight.

[0060] b. Add 50 mL of water and 50 g of the filtered graphite oxide stock solution into a beaker and mix to obtain a mixed solution;

[0061] c. subjecting the mixed solution obtained in step b to hydrothermal crystallization treatment at 140° C. under autogenous pressure for 12 h;

[0062] d. The manganese-based adsorbent material obtained after hydrothermal treatment was filtered and washed, dried at 80°C for 6 h, and then calcined at a temperature of 300°C for 4 h.

[0063] Example 2

[0064] The preparation method in Example 1 was adopted, except that in step d, the calcination temperature was 700° C. and the calcination time was 1 h.

[0065] Example 3

[0066] The preparation method in Example 1 is adopted, except that in step d, no calcination is performed.

[0067] Example 4

[0068] The preparation method in Example 1 was adopted, except that in step c, the hydrothermal crystallization temperature was 180°C.

[0069] Example 5

[0070] The preparation method in Example 1 is adopted, except that in step a, the amount ratio of the above-mentioned reactants is graphite: concentrated sulfuric acid: potassium permanganate: water = 1g: 50ml: 10g: 150ml; the manganese content in the filtered stock solution of graphite oxide is 41g / L as divalent manganese ions, the potassium content as potassium ions is 26g / L, the sulfur content as sulfate ions is 195g / L, and the carbon content as carbon atoms is 5.1g / L; the oxygen content of graphite oxide is 48% by weight, and the carbon content is 52% by weight.

[0071] Comparative Example 1

[0072] The preparation method in Example 1 was used, except that in step a, the mass ratio of potassium permanganate to graphite was 6 when preparing graphite oxide; the oxygen content of the graphite oxide was 33% by weight, and the carbon content was 67% by weight.

[0073] Test Case

[0074] The manganese-based adsorption materials and potassium permanganate of Examples 1 to 5 and Comparative Example 1 were tested as follows:

[0075] The XRD spectrum of the sample was obtained by a Rigaku D / MaxA-ⅢA X-ray diffractometer. Test conditions: Cu target Kα radiation, tube voltage 30 kV, tube current 20 mA, step scan, scanning range 5°~70°.

[0076] The average particle size of the prepared product was measured by scanning electron microscopy (ISI-60A electron microscope, ISI Company, USA, accelerating voltage 20 kV), and random sampling was performed for particle size statistics.

[0077] The element content of the sample was determined by XPS on a VGESCA-LABS X-ray photoelectron spectrometer, using Mg Kα X-rays as the laser source and the C1s binding energy (284.6 eV) of the surface contamination carbon to calibrate the binding energy of each element in the desulfurizer surface species.

[0078] The warm nitrogen adsorption and desorption test (BET) was carried out on a JW-BK200C surface area and pore size analyzer from Beijing Jingwei Gaobo Company. The surface area and pore volume were calculated using the two-parameter BET equation, and the pore distribution was calculated using the BJH method. The sulfide content in hydrogen after adsorption by the adsorbent was analyzed using an online chromatograph (Nexis-2030 from Shimadzu, Japan) and an SCD fluorescence detector (SCD-2030).

[0079] 290 mg of the examples and comparative examples prepared by the present invention and potassium permanganate as an adsorbent were loaded into the constant temperature section of the reactor of a passivated fixed bed micro reactor with an inner diameter of 12 mm and a length of 500 mm, and filled with quartz sand on the top and bottom. The volume content of hydrogen sulfide in the hydrogen raw material standard gas is 0.5%. Hydrogen is introduced at a flow rate of 30 ml / min at 40°C and 2.1 MPa for purification reaction. The hydrogen sulfide content in the purified hydrogen is analyzed online, and the analysis cycle is once every 5 minutes. The timing starts from the introduction of hydrogen, and the time until the hydrogen sulfide content in the purified hydrogen exceeds 0.004 ppm is counted as the penetration time. The penetration time test results of each sample are shown in Table 1, and other characterization results of each sample are shown in Table 2. The XRD pattern of the manganese-based adsorption material of Example 1 prepared by the present invention is shown in Table 1. Figure 1 shown.

[0080] Table 1

[0081]

[0082]

[0083] Table 2

[0084]

[0085] According to the test results in Table 1 and Table 2, it can be seen that the manganese-based adsorption material prepared by the preparation method provided by the present invention has a longer penetration time of hydrogen sulfide-containing hydrogen feed gas compared with the comparative example, and exhibits more excellent performance in the hydrogen purification reaction. The sulfide content in the purified hydrogen can meet the content requirements of sulfide impurities in hydrogen used in fuel cells, and the manganese element in the graphite oxide filtration stock solution is fully utilized, without the need to add additional manganese source, thereby reducing the preparation cost of manganese oxide.

[0086] It can be seen from the test results of Examples 1 to 6 that when the method for preparing the filtered stock solution of graphite oxide, the mass ratio of potassium permanganate to graphite when preparing graphite oxide, the element content in the filtered stock solution of graphite oxide, the hydrothermal crystallization treatment conditions, and the calcination conditions are within the specified range of the present invention, the effect and performance of the product prepared by the present invention can be further improved.

[0087] From the test results of Comparative Example 1 and potassium permanganate as an adsorbent, it can be seen that since the mass ratio of potassium permanganate to graphite in Comparative Example 1 is not within the scope of the claims, the hydrogen feed gas penetration time is significantly shorter than that of Examples 1 to 5, and therefore the performance of the prepared manganese-based adsorption material in the hydrogen purification reaction is worse than that of the embodiments of the present invention; and directly using potassium permanganate as an adsorbent, the hydrogen feed gas penetration time is even shorter, indicating that its adsorption performance in the hydrogen purification reaction is poor.

[0088] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0089] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0090] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a manganese-based adsorbent material and graphite oxide, the method comprising: S1 uses an improved Hummer method to prepare graphite oxide, and the obtained material is subjected to solid-liquid separation to obtain a liquid phase and a solid phase respectively. The liquid phase is the filtered stock solution, and the solid phase is recovered to obtain graphite oxide; S2 hydrothermally treat the filtered stock solution under hydrothermal autogenous pressure and atmosphere and recover the solid phase material; When preparing graphite oxide, the mass ratio of potassium permanganate to graphite is greater than 6.

5.

2. The method according to claim 1, wherein: Sodium nitrate and hydrogen peroxide are not added during the reaction of the improved Hummer method.

3. The method according to claim 1, wherein: The graphite oxide has an oxygen content of 35 to 60% by weight and a carbon content of 40 to 65% by weight.

4. The method according to claim 1, wherein: When preparing graphite oxide, the mass ratio of potassium permanganate to graphite is 8-15.

5. The method according to claim 1, wherein: In the filtered stock solution of the graphite oxide, the manganese content calculated as divalent manganese ions is 40-100 g / L, the potassium content calculated as potassium ions is 25-80 g / L, the sulfur content calculated as sulfate ions is 10-200 g / L, and the carbon content calculated as carbon atoms is 5-50 g / L.

6. The method according to claim 1, wherein: Step S2 includes: (1) mixing the filtered stock solution with optional water to obtain a mixed solution, wherein the mass ratio of the filtered stock solution to water is 1:(0-10); (2) subjecting the mixed solution to hydrothermal crystallization treatment, taking out a solid product, washing, drying and optionally calcining it to obtain the manganese-based adsorption material; Wherein, the hydrothermal crystallization conditions include: temperature of 100-200° C. and time of 2-72 h under autogenous pressure; The calcination conditions include: temperature of 250-700° C., time of 1-12 hours, and pressure of 0.1-1 MPa.

7. A manganese-based adsorption material prepared by the method according to any one of claims 1 to 6.

8. The manganese-based adsorption material according to claim 7, wherein: In the XRD spectrum of the manganese-based adsorbent material, characteristic peaks exist at 2θ positions of 12.2±0.5°, 24.7±0.5°, 36.8±0.5° and 66.3±0.5° respectively; The half-peak width of the diffraction peak at 12.2±0.5° is greater than 0.5°; The specific surface area of ​​the manganese-based adsorption material is 200 to 350 m 2 / g, pore volume is 0.2-0.9 ml / g; preferably, specific surface area is 240-320 m 2 / g, and the pore volume is 0.4~0.7ml / g.

9. The manganese-based adsorption material according to claim 7, wherein: Based on the mass of the manganese-based adsorption material, the manganese-based adsorption material has a Mn content of 25 to 53% by weight, an S content of 1 to 15% by weight, and a K content of 2 to 20% by weight; Preferably, the Mn element content in the manganese-based adsorption material is 40-53% by weight, the S element content is 2-12% by weight, and the K element content is 6-15% by weight.

10. A method for purifying hydrogen, the method comprising: contacting hydrogen with the manganese-based adsorption material according to any one of claims 7 to 9 at a temperature of 20 to 50° C. to perform a purification reaction; The reaction conditions of the hydrogen purification method include: temperature of 20-50°C, pressure of 0.1-5.0 MPa, and space velocity of 50-10000 h -1 ; The volume content of sulfide in the hydrogen is 0.1-1%, and the content of sulfide in the hydrogen is calculated as hydrogen sulfide.

Citation Information

Patent Citations

  • Graphene material and preparation method thereof

    CN103771394A

  • Preparation method of graphene based lithium ion battery composite negative electrode material

    CN103896260A

  • Recycling method for waste acid generated during preparation of graphite oxide through liquid-phase chemical method

    CN106396227A

  • Reduced graphene oxide / manganese oxide compound and preparation method thereof

    CN107104002A

  • Manganese dioxide and preparation method and application thereof

    CN110040782A